2015
DOI: 10.1021/la503889j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Nitrite and Nitrate Electrocatalytic Reduction through the Employment of Self-Assembled Layers of Nickel- and Copper-Substituted Crown-Type Heteropolyanions

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 72 publications
(110 reference statements)
2
16
0
1
Order By: Relevance
“…3) for all HPAs. The deposition of AgNP or HPA layers leads to a consistent decrease or increase in RCT respectively, which is consistent with our previous studies [58] and is also confirmed by cyclic voltammetric measurements (data not shown) . Firstly, this effect can be probably due to the high conductivity of the metal nanoparticles, which facilitate the electronic communication between the probe molecules and the underlying electrode surface [69,70].…”
Section: Electrochemical Impedance Spectroscopy (Eis)supporting
confidence: 92%
See 3 more Smart Citations
“…3) for all HPAs. The deposition of AgNP or HPA layers leads to a consistent decrease or increase in RCT respectively, which is consistent with our previous studies [58] and is also confirmed by cyclic voltammetric measurements (data not shown) . Firstly, this effect can be probably due to the high conductivity of the metal nanoparticles, which facilitate the electronic communication between the probe molecules and the underlying electrode surface [69,70].…”
Section: Electrochemical Impedance Spectroscopy (Eis)supporting
confidence: 92%
“…In addition, the first reduction peak current of the W-O I redox process is higher than that observed for other HPAs, which reflects the contribution from reduction of Cu 2+ -center. The presence of the Fe 3+ -center ( Interestingly the redox processes associated with the Cu 2+ -and Fe 3+ metal centres in the HPA moieties disappear upon layer formation, which is in agreement with literature data for mono-substituted HPAs [58,66,67] and represents the phenomenon of electrostatic interaction between the HPA and the encapsulating multilayer film.…”
Section: Characterization Of Agnp By Uv-vis Spectroscopysupporting
confidence: 91%
See 2 more Smart Citations
“…The calibration plot showed two linearity regions, which probably illustrates the complexity of the electrocatalytic process occurring at the LBL film. The sensitivity of nitrite detection estimated at the linearity region of 0.2-0.6 mM was 132 mA M cm -2 , which is larger than the reported values of sensitivity obtained at different filmmodified electrodes for electrocatalytic reduction of nitrite [39][40][41][42][43][44][45][46]. The significant decrease of sensitivity down to 15.7 mA M cm -2 was observed at linearity region of higher nitrite concentrations (0.6-5 mM).…”
Section: Preliminary Electrocatalytic Properties Of Lbl Filmsmentioning
confidence: 61%